2012
DOI: 10.3390/ma5050922
|View full text |Cite
|
Sign up to set email alerts
|

Surface Fractal Analysis for Estimating the Fracture Energy Absorption of Nanoparticle Reinforced Composites

Abstract: In this study, the fractal dimensions of failure surfaces of vinyl ester based nanocomposites are estimated using two classical methods, Vertical Section Method (VSM) and Slit Island Method (SIM), based on the processing of 3D digital microscopic images. Self-affine fractal geometry has been observed in the experimentally obtained failure surfaces of graphite platelet reinforced nanocomposites subjected to quasi-static uniaxial tensile and low velocity punch-shear loading. Fracture energy and fracture toughnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
1
17
0
1
Order By: Relevance
“…Moreover, tremendous drop in mechanical properties (energy absorption) is more pronounced with adding xGnP rather than that associated with nanoclay reinforcement. On the contrary, another study reported 10% improvement in impact energy absorption with addition of 2.5 wt % graphite platelets to brominated resin 7…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, tremendous drop in mechanical properties (energy absorption) is more pronounced with adding xGnP rather than that associated with nanoclay reinforcement. On the contrary, another study reported 10% improvement in impact energy absorption with addition of 2.5 wt % graphite platelets to brominated resin 7…”
Section: Resultsmentioning
confidence: 95%
“…Bromination outcome on punch shear characteristics for laminated face sheets and sandwich composites of vinyl ester nanocomposites was investigated using Dynatup 8250 drop‐weight impact instrument 7. Test results showed that more than 10% improvement in impact energy absorption with addition of 2.5 wt % graphite platelets to brominated resin.…”
Section: Introductionmentioning
confidence: 99%
“…Возможность выхода из строя зонда СТМ, приводящее к искажению визуальной картины поверхности образца и изменения параметров проводимости между образцом и зондом, существенно ограничивает применение СТМ для изучения больших площадей образца с высоким разрешением. Исходя из вышеизложенного, можно с уверенностью утверждать, что результаты моделирования процесса взаимодействия зонда СТМ с поверхностью образца будут способствовать получению точной измерительной информации о геометрических параметрах поверхности образца и электрических характеристиках наноструктур и острия, что находит важное практическое применение при изучении, например, фрактальных структур, обладающих принципиально новыми физико-химическими свойствами [20][21][22][23][24][25].…”
Section: заключениеunclassified
“…Thermoset polymer vinylester is among the most widely used polymers due to its excellent barrier and thermal properties, chemical stability, corrosion resistance, light weight, low cost, and ease of processing [27][28][29]. Pure vinylester is brittle; to overcome this limitation, the resin is reinforced or reacted with various fillers or modifiers [30,31]. The most often used filler material with pure vinylester is glass fiber.…”
Section: Introductionmentioning
confidence: 99%